Increasing frequency and severity of odontogenic infection requiring hospital admission and surgical management. Issue 4 (May 2020) - Fu, B.; McGowan, K.; Sun, J.H.; Batstone, M.
Abstract: Odontogenic infections can become life-threatening if not managed in a timely manner, and they increase the physical cost of treatment to the patient and the financial cost to the public health system. We investigated the number of admissions to a Queensland tertiary hospital within a decade, and differences in the patients' characteristics, severity at presentation, and clinical outcomes. We compared patients with odontogenic infections who were taken to theatre at the Royal Brisbane & Women's Hospital (RBWH) between January 2003 and December 2004 with those treated between January 2013 and December 2014, a total of 292. Data on demographics, presentation, previous history, antimicrobial treatment, and admissions, were collated and analysed. There were no significant differences in demographics. In the 2013/2014 group there was a two-fold increase in infections related to lower third molars (p = 0.001), a 50% increase in trismus (p = 0.001), and a 20% increase in submandibular swelling (p = 0.010). The percentage of patients admitted to the intensive care unit (ICU) was three and a half times higher in the 2013/2014 group (p = 0.001). The presentation of odontogenic infections has increased in the decade from 2003/2004 to 2013/2014. Measures of the severity of disease have increased, while the basic characteristics of the patients have remained constant. Improved primary preventative measures and early interventions are therefore needed to alleviate the burden that these infections place on the public health system.